Miniature Differential Mobility Analyzer for Compact Field-Portable Spectrometers - Qi, Chaolong (Aerosol science and technology : the journal of the American Association for Aerosol Research, 2016)
A low-flow miniature differential mobility analyzer (mDMA) has been developed for compact field-portable mobility spectrometers to classify the submicrometer aerosol. The mDMA was designed for an ultra-low aerosol flow rate of 0.05 L/min. At a sheath flow rate of 0.2 L/min, the mDMA's upper size limit was estimated to be about 921 nm. The mDMA has a classification zone of 2.54 cm long, an outer diameter of 2.54 cm, and an inner diameter of 1.778 cm. The design allows low-cost fabrication and easy assembly. Tandem DMA (TDMA) measurements were carried out to evaluate the performance of the mDMA. Its transfer function was described using Stolzenburg's model. The experimentally measured transfer function shows close agreement with the theory. The transmission efficiency was comparable to that of the Knutson-Whitby DMA for particles in the range of 10-1000 nm. The mobility resolution was comparable to that of the TSI 3085 nanoDMA at the same aerosol flow rate. The design features and performance of the mDMA make it suitable for compact field portable mobility size spectrometers for measurement of nanoparticles and submicrometer aerosol